Pengaruh Molaritas Dan Rasio Aktivator Pada Geopolimer Untuk Pengolahan Air Gambut - Kartika Pratama Syafitri; Edy Saputra; Lita Darmayanti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Peat water is the brownish red water that come from the surface of peat soil with high organic content, pH 2-5, and low harness level. Geopolymer is the silicate alumina inorganic compound which synthesized by some materials such as fly ash, kaolin and rice husk ash. The chemical composition like zeolite, that structurally composed from macromolecules chain which consist of silicon atomics, aluminium, and oxygen. This research make use of geopolymer from kaolin as the adsorbent which reduced color, organic content, and increasing pH of peat water with Permenkes No.416/MENKES/PER/IX/1990. In the research make use of molarity variation NaOH 10, 12, 14, 16 M and activator ratio 0,4, 0,5, 0,6 at geopolymer to treatment peat water. The result of this research is treatment peat water with geopolymer 16 M – 0,6 that capable to make pH (become) 6,8, color (integrity) 0 Pt-Co and organic content 3,16 mg/L KMnO4.Keyword: Peat water, geopolymer, molarity, activator ratio, color, organic content, pH